Políticas públicas vigentes de salud mental en Suramérica: un estado del arte (2016)
ABSTRACT: To present the state of the art regarding the content of the public mental health policies currently in force in South America in order to establish an overview of the scope and limitations of the regulations on the subject in the region. Methodology: a documentary study with a hermeneutic approach explaining the relationships between the contents of the public policies for mental health and the context of the South American countries. For the analysis, we included normative documents of the countries, e.g. agreements, resolutions and acts. Similarly, academic papers from the period between 2003 and 2013 were included. These made it possible to describe and analyze the research subject. Results: countries such as Colombia, Argentina, Paraguay, Brazil, Peru, Ecuador and Uruguay have current regulations (agreements, resolutions and acts) supporting the content of public policies in regards to mental health. On the other hand, Chile, Bolivia and Venezuela base their policies on administrative mechanisms (programs, plans and projects) without enforcing mandatory compliance. Conclusion: the notion of mental health underlying each national policy emphasizes health promotion and prevention equally, and is based on a positive conception of well-being that highlights the active role of subjects and populations as well as the capabilities and liberties available. Nevertheless, their resources, strategies, actions and goals are based on a biomedical model that prioritizes the diagnosis and treatment of mental disorders.